Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.